ANALYSIS OF FERMENTED RICE BRAN, PHOSPHATE INTAKE, AND SODIUM INTAKE ON BLOOD PRESSURE: A REVIEW: Analisis Pengaruh Fermentasi Rice Bran, Asupan Fosfat, dan Natrium Terhadap Tekanan Darah - Azizah Afifah; Endang Widajati; Rany Adelina (Program Studi Gizi, Fakultas Kesehatan Masyarakat, Universitas Binawan, 2023)
The number of people with hypertension continues to increase every year. Several foods contain nutrients that can affect blood pressure. They are rice bran fermentation, phosphate intake, and sodium intake. This study aims to analyze the effect of fermented rice bran, sodium, and phosphate intake on blood pressure through a review of literature. This research is a literature narrative study. That is the analysis of fermented rice bran, phosphate intake, and sodium effect on blood pressure. Seven kinds of literature met the inclusion criteria, with most of the designs being cross-sectional and experimental study designs with a large sample of the majority of the top 20 human respondents and more than ten experimental animals (rats). The results showed that fermentation of rice bran could lower blood pressure through ACE (Angiotensin-Converting Enzyme) inhibitor compounds that inhibit angiotensin I turning into angiotensin II with a p-value<0.05 in experimental animals (rats). In addition, a high intake of phosphate or sodium can increase blood pressure By narrowing of blood vessels and make the heart work heavier with a p-value<0.05 in the healthy human subject, hypertension sufferers, and experimental animals (rats). Rice bran fermentation has significantly reduced (rat) blood pressure. High intake of phosphate or sodium can increase blood pressure in healthy humans, hypertensive patients, and animal studies.